Processing insect abundance: trading and fishing of zazamushi in Central Japan (Nagano Prefecture, Honshū Island). Issue 1 (December 2015) - Césard, Nicolas; Komatsu, Seiji; Iwata, Akihisa
Abstract Background This article presents the links between technique, commerce and consumption in fishing for zazamushi, a mixture of aquatic insect larvae sold as food souvenirs in Japan. Since zazamushi are mainly collected for economic reasons, we suggest that demand for them has incited technical development among collectors in order to fish more insects. Methods Several fishermen and traders were interviewed in semi-directed interviews about their practices and knowledge. To understand the passage from a faunal composition to a commercial composition, our research follows a fishing session closely, as well as the selection of insects that follows it. The insects collected were separated from inanimate matter, then identified, counted and weighed at each stage of the process. Results Our results suggest that the current technique corresponds to an evolution in subsistence and recreational collecting towards a more systematic fishing of the insects, the aim of which is commercial. In their response to trade issues, the collectors have moved away from the banks to fish the insects in the river current, thus increasing the amount of one species captured compared to another. Although the technique is efficient (and similar to other harvesting techniques), it requires the thorough sorting of organic debris and insects (in our example, the catch contains approximately 78 % of inanimate matter and 22 % of insects, of which 3.29 % are retained for consumption, i.e., less than 2 out of 100 insects). The selection of insects to be consumed takes place mainly during cleaning. This stage depends on traders and reflects the different compositions sold as souvenirs. Conclusions Our research shows that the consumption of insects is not explained just by ecological factors that are favourable or unfavourable, but also by technological and economic factors related to their commerce. It suggests that the traders have gradually established the insects that are currently sold as zazamushi and that this commercial development may have had an influence on the preference for insects consumed. It also shows that the cleaning of the insects constitutes an important stage prior to their consumption, one that should not be underestimated.